Globalization, value change, and generations : a cross-national and intergenerational perspective - Ester, P.; Braun, Michael, 1956-; Mohler, Peter Ph., 1945- (European values studies ;, 2006)
Values are a hot topic in Europe, both in the public and political debate as well as in the social sciences. Is Europe a community of values? What are the cultural borders of the European Union? How united are Europeans with respect to their fundamental values? How does globalization affect European values? Do national values vanish? There is also a clear moral overtone in the debate: basic values are believed to erode, community values are waning, values become fragmented, and civic engagement is rapidly declining while hedonism and consumerism are prevailing. But are these far-reaching assumptions true? Answers are provided in this book. The three core issues that guide the various chapters in this book are the following: do basic values in European countries converge or diverge? Do we observe a marked decline in traditional values in European societies? Is it the youngest generation in Europe that embraces new values?.